KCPR Talk Radio Show, ca. 1982 - Brad Loney::::::host:::; Carol Myer::::::host::: (1982)
Recording of the KCPR Talk Radio Show, hosted by Brad Loney and Carol Myer. The topic of the show explores the consequences and effect of Cal Poly not offering a summer school session, which was then recently announced as a possibility by President Warren Baker. Loney and Myer first interview a Cal Poly administrator, Howard West, then discuss the topic among themselves and several call-in listeners. The recording abruptly ends at the 48-minute mark, and then resumes at [00:53:43] with a short recording of reversed sped-up vocals. That portion of the recording has been left out of the audio here.[00:00:00] Promo for Cal Poly Career Services [00:00:49] KCPR Talk Radio Show opening [00:01:20] Introductions by KCPR talk radio show hosts Brad Loney and Carol Myer, and introduction of the show's topic, the possibility of no summer school session or quarter [00:01:50] Interview with Howard West, Associate Executive Vice President of Cal Poly, begins [00:09:02] Interview with West ends [00:13:26] Hosts begin taking calls from listeners [00:20:38] Program break [00:44:40] Program wrap-up [00:45:55] Mike Dawson's 'Album Review' program promo [00:46:42] Program promo for 'Future Shock' (Evan) [00:47:34] Open Channel program begins [00:48:00] Recording on tape ends abruptly